The impact of education levels and paths on labor market outcomes in South Korea: Focusing on vocational high school graduates. Issue 1 (2021) - Choi, Seonkyung
Abstract: The predominant perception in South Korea is that the route to the best jobs is to attend university. Even two-thirds of vocational high school graduates now go to university. This paper examines the impact of different education paths on employment and wages. Unlike previous research, it takes account of Korea's unusual education system. It uses not only probit and ordinary least squares models but also a conditional expectation correction method model to tackle unobserved heterogeneity. The paper finds vocational secondary education followed by direct entry into the labor market yields better employment status and wages than higher education, when controlling for family and individual characteristics. This result challenges the appropriateness of Korea's current education strategy of maximizing higher education enrollments. Highlights: South Korea's education system is based on the idea that university education leads to the best jobs. This paper takes account of Korea's unusual education paths unlike previous papers. The paper also tackles endogeneity problems ignored by previous research. Secondary vocational education has better labor market possibilities. This implies a need to rethink Korea's education strategy of maximizing higher education for all.